An entrepreneurial intention model focussing on higher education. Issue 7 (19th March 2020) - Tomy, Sarath; Pardede, Eric
Abstract : Purpose: Start-up intention among university students is related to the image of entrepreneurship as a career alternative. University is critical in developing the levels of motivation and capabilities of graduates to effectively engage in entrepreneurial activity. The purpose of this paper is to propose an entrepreneurial intention model focussing on higher education and the implementation of the model as a practical digital application which can be used in universities to improve the entrepreneurial intention of students enrolled in different courses. Design/methodology/approach: This paper first discusses the importance of entrepreneurial intention in graduate entrepreneurship. Then, it proposes an entrepreneurial intention model based on the four propositions identified from the literature. Finally, the model is implemented as a practical digital application focussing on self-skill awareness, entrepreneurial resources and entrepreneurial support network. A survey is conducted with students to evaluate the model and the application. Findings: Entrepreneurial awareness found to have a positive effect of entrepreneurial intention. Besides the conceptual model, this study has developed a digital application to enhance entrepreneurial intention of students focussing on information technology discipline. The application is evaluated through an online survey and the results show that the application can significantly improve entrepreneurial intention. Originality/value: The proposed entrepreneurial intention model and the digital application offer guidance to universities as to how online systems can be used to create an environment that fosters individual intentions to select entrepreneurship as a career option, even for students doing non-entrepreneurial courses.